A review of reported stakeholder engagement in early-stage translational research - Thomas W. Concannon; Marguerite Fenwood Hughes; Amy E. LaVertu; Jonathan Garlick; Alice M. Rushforth (Journal of Clinical and Translational Science)
Abstract